Human Rights and the Environmental Protection: The Naïveté in Environmental Culture - Anggriawan Wisadha, Made Adhitya; Widyaningsih, Grita Anindarini (Udayana Journal of Law and Culture; Vol 2 No 1 (2018): Maintreaming Socio - Cultural Policy, 2018)
There are growing trends in the human rights to substantially extend the values to protect the environment or moreover to welcome the ideas of the rights to environment, not to mention the rights of environment. The purpose is to inclusively embrace the environmental problems wherein the humanity challenges posited on, but this agenda may leave a room of doubt how far the human rights body can address the environmental destruction as it needs the interplay of culture and environmental ethics to promoting such concepts. Therefore, this paper aims to identify the justification of how human rights in the environmental protection in the contemporary discourse are bringing to light, as many current cases attempt to linkage the environmental approach to the human rights instrument, such as the rights to life, healthy environment, and intergenerational equity. To analyse further, the theoretical framework in this paper will be explicated by environmental culture paradigm which illustrates the egalitarian concept between human and environment to elicit the clear thoughts of how human rights is naïve to protect the environment. This article will firstly depict the human rights and the environmental protection discourse and then, explore the naïveté narratives of environmental culture about the ecological crisis roots that are fundamentally anthropogenic, as to reflect the ground realities how this nexus will play out. Finally, this paper found the moral justification per se relies on the effort of elaborating the human prudence in their relationship with nature, albeit bringing the naïveté.